A Descriptive Study on the TPACK Knowledge of Biology Teachers in Sragen Regency, Central Java - Sendy Putra Pradana; Advend Sri Rizki Sianturi; Muhammad Khoirul Antony; Ahmad Naharuddin Ramadhan (BIOPENDIX, 2025)
In the context of rapid digital transformation, the integration of the TPACK (Technological Pedagogical Content Knowledge) framework has become increasingly vital for educators—especially those teaching biology—to facilitate the incorporation of technology into instruction and promote deeper student comprehension of complex topics. TPACK comprises three foundational areas: Technological Knowledge (TK), Pedagogical Knowledge (PK), and Content Knowledge (CK), as well as their interrelated domains: Pedagogical Content Knowledge (PCK), Technological Content Knowledge (TCK), and Technological Pedagogical Knowledge (TPK). This study investigates the extent to which high school biology teachers implement the TPACK components. Employing a descriptive research design with a test-based approach, the study targets a hypothetical population encompassing all senior high school biology teachers in Sragen Regency—past, present, and prospective. A convenience sampling technique was applied, selecting 17 currently active biology teachers from 13 senior high schools across the region. Data collection utilized a structured test instrument designed to evaluate teachers’ comprehension of TPACK concepts. Results indicate that the participants generally possess a moderate level of knowledge regarding the application of TPACK in teaching.